The competitiveness of rural areas in the Republic of Tatarstan - Sitdikova, Landysh; Heijman , Wim; van Ophem, Johan (Applied Studies in Agribusiness and Commerce, 2013)
This paper analyses the main factors influencing the regional competitiveness of rural areas in the Tatarstan Republic. Firstly, 19 variables related to the socio-economic situation in the Tatarstan Republic were analysed, these having been taken from the Statistics Committee of the Tatarstan Republic. Principal component analysis (PCA) was then used to determine the weights of 10 indicators that have an effect on the level of regional competitiveness. Factor weights are used as weights in the summation of the standardised scores of variables that have an impact on competitiveness. The major factors influencing the level of regional competitiveness are the level of economically active population, investment in housing and the level of education. The following results were obtained: one of the 44 regions is very highly competitive and two are highly competitive; two of 44 regions have a medium level of competitiveness and 39 regions have a low level of competitiveness.